KEANEKARAGAMAN HYMENOPTERA PARASITIKA PADA TIPE EKOSISTEM BERBEDA DI BANGKA TENGAH, KEPULAUAN BANGKA BELITUNG - Saputra, Herry Marta; Maryana, Nina; ., Pudjianto (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Diversity of parasitic Hymenoptera in different ecosystem types in Central Bangka, Bangka-Belitung Islands.Hymenoptera richness is dominated by parasitic species. More than 80% of Hymenoptera play a role as parasitoid on arthropods that are mostly insects. Diversity of parasitic Hymenoptera is widely studied in various types of terrestrial ecosystems including agro-ecosystem and non-agro-ecosystem. This study aimed to invent and compare the diversity of parasitic Hymenoptera in three different ecosystems, i.e., forest, oil palm plantation, and ex-tin mining. The location was located in Central Bangka Regency, Bangka Island. The study was conducted in Juli 2014 until October 2015. Parasitic Hymenoptera was collected with insect sweep net and yellow pan trap on one transect line with 1000 m length. Parasitic Hymenoptera were found on forest as much as 732 morphospecies, 326 morphospecies on oil palm plantations, and 293 morphospecies on ex-tin mining. Diversity and abundance of parasitic Hymenoptera on forest was higher than oil palm plantation and ex-tin mining area. Braconidae family was found dominant on forest, however on oil palm plantation and extin mining area the dominant family was Scelionidae.